2022
DOI: 10.1002/chem.202200755
|View full text |Cite
|
Sign up to set email alerts
|

How the Chalcogen Atom Size Dictates the Hydrogen‐Bond Donor Capability of Carboxamides, Thioamides, and Selenoamides

Abstract: The amino groups of thio-and selenoamides can act as stronger hydrogen-bond donors than of carboxamides, despite the lower electronegativity of S and Se. This phenomenon has been experimentally explored, particularly in organocatalysis, but a sound electronic explanation is lacking. Our quantum chemical investigations show that the NH 2 groups in thio-and selenoamides are more positively charged than in carboxamides. This originates from the larger electronic density flow from the nitrogen lone pair of the NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…24 Previous studies have proved the reliability of this level of theory for the evaluation of the hydrogen bonding interaction mechanism within weakly-bound complexes. [25][26][27] The bonding energies of the hexamers, as well as their subunits, i.e., dimers, trimers, tetramers and pentamers, were computed using eqn (1):…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Previous studies have proved the reliability of this level of theory for the evaluation of the hydrogen bonding interaction mechanism within weakly-bound complexes. [25][26][27] The bonding energies of the hexamers, as well as their subunits, i.e., dimers, trimers, tetramers and pentamers, were computed using eqn (1):…”
Section: Methodsmentioning
confidence: 99%
“…The electron charge distribution has been analyzed within the Voronoi Deformation Density (VDD) analysis. 4,30 Fig. 1 Structure of a G-C Janus-type monomer, referred to as AAD in the present study (left), and the schematic structure of the rosette derived from the AAD monomer (right).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] based on dispersion‐corrected relativistic density functional theory at the ZORA‐BLYP‐D3/TZP level for geometry optimizations and ZORA‐BLYP‐D3/TZ2P for energies. Previous works[ 22 , 23 , 24 ] have shown that this level of theory gives excellent understanding of bonding mechanism in hydrogen bonding and also in long range interactions within weakly‐bound complexes. [11] Furthermore, the use of the TZP basis set for large supramolecular systems has shown to furnish accurate results.…”
Section: Methodsmentioning
confidence: 99%
“…In all these complexes, nevertheless, hydrogen bond acceptor is an O atom, the prime member of the chalcogen group. , In recent times, attention was drawn to the other chalcogens also but mostly pertained to Se, Te, etc., especially to evaluate competitiveness with respect to halogen bonding. However, there has only been a little focus on S-based supramolecular assemblies despite the fact that such compounds are so much well known for their significance in various biological processes in the form of peptides and also as precursors for many chemical transformations in the domains of natural product synthesis, bioinorganic complexes, polymers, etc.…”
Section: Introductionmentioning
confidence: 99%